Educational Attainment and Life Expectancy. (October 2014) - Kaplan, Robert M.; Spittel, Michael L.; Zeno, Tia L.
National objectives for health concentrate on improving life expectancy and enhancing health-related quality of life. Although U.S. life expectancy has seen significant extensions over the last century, the rate of increase has been falling behind other wealthy countries, and these trends have been worsening over the last 30 years. In addition, the United States spends considerably more on health care in comparison with major trading competitors. Most policy approaches for enhancing health focus on increasing expenditures for medical care. Yet, medical care explains only about 10% of the variance in health outcomes, whereas behavioral and social factors outside of health care explain nearly 50%. Evidence suggests that educational attainment may be one of the strongest correlates of life expectancy. As a baseline, cancer screening and optimizing established risk factors for premature death typically extend life expectancy by less than 1 year. In contrast, remediating the health disparity associated with low educational attainment might enhance life expectancy by up to a decade. Amassing persuasive evidence on the health benefits of interventions to improve educational attainment will be challenging. To address this issue, a robust program of systematic research is needed.